KAJIAN KOMPETENSI SISWA DESAIN PEMODELAN DAN INFORMASI BANGUNAN SMK NEGERI 7 BALEENDAH DALAM KEGIATAN PRAKTIK KERJA LAPANGAN DI INDUSTRI DAN DUNIA KERJA - Muhammad Fulqhihaqq Irviansyah, - (2023)
Vocational education is one of the government's focuses in developing human resources (HR) and has an equally important role as infrastructure development, because vocational education has a strategic position to produce human resources who are competent, productive and have global competitiveness. One of the programs in Vocational High Schools (SMK) to produce quality human resources is through the Field Work Practice (PKL) program with industries according to their fields. However, vocational education, which is expected to be a link and match between schools and industry, has not met expectations. Therefore this study aims to examine the competencies produced by graduates of SMK Negeri 7 Baleendah majoring in Building Modeling and Information Design (DPIB) and to examine the application of these competencies when students carry out field work practice programs in industry and the world of work (IDUKA). The research method used is a qualitative research method. Data collection techniques using interviews, observation and field studies. The analysis used in this study uses the qualitative data analysis model version of Miles and Huberman. The results of the study show that the provision of competencies provided by the DPIB department of SMK Negeri 7 Baleendah and their application in the PKL activity program are appropriate and oriented towards IDUKA in the aspects of competency preparation, competence in their fields, KKNI competencies, and world of work competencies.